Por detrás da máscara: o olhar das crianças sobre a pandemia da Covid-19 - Clemente, Joana Cantídio Mota (2021)
This study comprises the recording and analysis of the scenes experienced and perceptions of children inserted in vulnerable communities in Ceará municipalities during the COVID-19 lockdown, through a qualitative research where three thematic pills were produced: (1) what is the coronavirus, (2) games in the home environment and Family relationships and (3) post- pandemic perspective. The research revealed in children the fear of the vírus combined with losing someone they love, the understanding of physical distance, use of alcohol and mask. It i salso possible to perceive a solitary playing where “playing” becomes whatching TV and using the cell phone, evidencing the increase in the use of screens in this period; negative changes in Family relantionships and the immense desire to returno to face-to-face activities.